Blind source separation aided characterization of the γ′ strengthening phase in an advanced nickel-based superalloy by spectroscopic 4D electron microscopy. (1st April 2016) - Rossouw, David; Krakow, Robert; Saghi, Zineb; Yeoh, Catriona S.M.; Burdet, Pierre; Leary, Rowan K.; de la Peña, Francisco; Ducati, Caterina; Rae, Catherine M.F.; Midgley, Paul A.
Abstract: The γ′ strengthening phase in an advanced nickel-based superalloy, ATI 718Plus, was characterized using a blind source separation applied to a four dimensional X-ray microanalysis dataset obtained by scanning transmission electron microscopy. Selected patterns in the X-ray spectra identified by independent component analysis were found to be spatially and chemically representative of the matrix (γ) and precipitate phases (γ′) present in the superalloy, enabling their size, shape and distribution to be determined. The three dimensional chemical reconstruction of the microstructure may provide insight into the role of the various alloying elements in the evolution of the microstructure at the nano-scale. Graphical abstract: